You ask and do not receive, because you ask wrongly - Kelly, Christopher E (International journal of police science & management, 2021)
Investigative interviewing can be thought of as the interaction between two clusters of factors: questions and techniques. Analyses of question types and interview techniques are often treated discretely, where one is the focal point at the expense of the other, or they are conceptually indistinguishable. To explore these relationships further, the current study examined a sample of interviews using the Griffiths Question Map and a taxonomy of interview methods. In addition to presenting maps as example interviews, the article explores the associations between interview clusters and suspect cooperation. Results indicate that greater use of appropriate questions was associated with greater use of rapport-building techniques and greater suspect cooperation, and a reduction in the use of accusatorial interrogation tactics, which themselves were associated with suspect resistance. Implications for research and practice include understanding the interaction between these—and potentially other—clusters.